Tritium in precipitation on 5 sites in North-West France during the 2017–2019 period. (February 2020) - Connan, O.; Maire, D.; Hébert, D.; Solier, L.; Laguionie, P.; Rozet, M.; Lamotte, M.; Maro, D.
Abstract: Between October 2017 and May 2019, measurements of tritium in rainwater were carried out at several sites in north-west France. Tritium is an important tracer for hydroclimatic studies and this work provided up-to-date data that we compared with Global Network for Isotopes in Precipitation (GNIP) measurements. Of the various sites studied, some could potentially be affected by atmospheric gaseous emissions from the nuclear industries in the region (reprocessing plant, nuclear power plant). On our reference site, the activities measured in rainwater are often below the decision threshold (<0.15 Bq.L −1 ). Two other sites with little impact from nuclear industries have mean activities of less than 0.7 Bq.L −1 . At the two Cherbourg sites closer to the nuclear industries, the activities in rainwater are slightly higher on average, though still close to 1 Bq.L −1, but the activities are more variable when the rainfall accompanies an air mass from the Orano La Hague nuclear site. Using existing GNIP data and a simple model to simulate predicted data up to 2019, it is shown that all our measured data are comparable with the predicted activities for GNIP stations with a marine influence, in the case of the reference site and the sites with little impact from nuclear industries, and for GNIP stations with a continental influence, in the case of the other sites. Seasonal variation in activities was detected, with greater activities in the spring-summer period corresponding to the well known 'spring leak' phenomenon. This study also reveals significant differences between the activities measured on the western side of France (influenced by the Atlantic Ocean) and those measured in a continental zone. The mean levels of tritium in rainwater in France, excluding any nuclear influence, can be estimated on average at less than 0.3 Bq.L −1 in the western marine zone, and at around 1 Bq.L −1 in the continental zones. Highlights: Measurements of 3H in precipitation. Various sites in north west of France. Influence of Nuclear facilities. Influence of seawater and prevailing winds.